The Visionaries profiles IITA on public TV - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
The national documentary series The Visionaries is profiling IITA in its current season. The documentary was shot on location in Tanzania, Kenya, and Nigeria.